The 'opt-out' approach to deceased organ donation in England: A misconceived policy which may precipitate moral harm. (June 2019) - Cantrell, Tobias K
In an effort to solve the shortage of transplantable organs, there have been several proposals to introduce an opt-out approach to deceased organ donation in England (also termed 'deemed', or 'presumed' consent). In seeking to enact the so-called 'opt-out proposal' via an amendment to the Human Tissue Act 2004, The Organ Donation (Deemed Consent) Bill 2017–19 represents the most recent attempt at such legal reform. Despite popular calls to the contrary, I argue in this paper that it would be premature for England, or, indeed, any country, to adopt an opt-out approach at this time. Not only is the available evidence inconclusive on whether introduction of the opt-out proposal would increase the supply of transplantable organs (a common misconception), but there is also a chance that doing so might bring about an otherwise avoidable moral harm through an unjustified interference with individual autonomy. I maintain that the resources required to change the law to such effect would be better expended on alternative, provenly efficacious and less contentious mechanisms for increasing the supply of transplantable organs, such as: improving communication with the family of the deceased, developing infrastructure, raising public awareness and enhancing staff training, attitudes and understanding towards organ donation.